Efeitos do aumento da temperatura sobre a disponibilidade hídrica para a pecuária familiar na sub-bacia do Alto Camaquã, RS - Rocha, Nájila Souza da (2016)
This study aimed to analyze the vulnerabilities of family livestock on water front property at temperature rise caused by climate change, the Alto Camaquã s sub-watershed, which is located at the top of the river basin Camaquã covering eight counties of Rio Grande do Sul, all belonging to the Pampa Biome. This territory belongs to the remaining part of greater value to the biodiversity of the Pampa Biome, it includes a region that, for their economic, social and environmental characteristics, still maintains an ecosystem stable priori, still preserving some plant systems, water and nature of the local geology. The production system, family farming, helps to maintain these conditions, but suffer certain market demands incompatible with their management. In addition, climate and environmental changes that have occurred throughout the planet, accelerate weathering processes, environmental degradation and changes the hydrological cycle. The availability of water becomes a major environmental and social problems of the region. For these and many other features, the Alto Camaquã can be considered a fragile and vulnerable sub-watershed to the various socio-environmental changes, including climate change. This research was divided into two main analyzes: the first analysis deals with the Water Balance Climatologically (BHC), carried out in order to understand the behavior of the basin for the months of higher deficits and water surplus. The second analysis deals with the weaknesses of the Alto Camaquã front of the temperature rise caused by climate change and the vulnerability of family farmers face these changes. The BHC was performed by two methods: the first methodology consisted in calculating the Water Balance Climatological (BHC) Thornthwaite and Mather (1995), excel spreadsheet for Windows. The second method consisted in calculating the BHC through script GERHI, this was used a script developed by GERHI (Water Resources Management) of UFSM. The methodology used for the analysis of environmental weaknesses, was adapted from FRAG-RIO project (MMA, 2009), through a scheme weights (for variables) and notes (for classes). This study shows that water availability and soil resistance are variables that make the Alto Camaqua a fragile front territory to temperature rise caused by climate change. In addition, family farmers are vulnerable to these changes do not present mitigation instruments of environmental impacts and no increased its resilience strategies.